Factors Influencing the Performance of Volleyball Athletes: A Review of the Literature - Sihombing, Yobel Martua; Maulana, Muhammad Ridho; Simatupang, Franroso Pininggit; Gea, Arman; Melisah, Melisah (Jurnal Inovasi Olahraga, 2025)
Purpose of the study: This systematic literature review aims to identify and analyze the factors that influence volleyball athlete performance through a comprehensive examination of scientific literature published between 2004-2025. Materials and methods: A systematic literature review was conducted using SPORTDiscus and PubMed databases. Studies were selected based on predefined inclusion criteria focusing on volleyball performance factors, training interventions, and game-related statistics. Data extraction was performed using a standardized protocol, and findings were synthesized qualitatively. Results: Analysis of 55 studies revealed that volleyball performance is influenced by multiple interconnected factors including technical skills (attack success, serve effectiveness, blocking proficiency), physical attributes (agility, explosive power, VO2max endurance), psychological factors (athlete well-being, coaching quality), and tactical elements (game-related statistics). Performance determinants varied by gender, with women's teams showing stronger correlation with attack attempts and team errors, while men's teams demonstrated greater dependence on serve points and blocking effectiveness. Conclusions: Volleyball athlete performance is multifactorial, requiring integrated training approaches addressing technical, physical, psychological, and tactical components. Evidence supports that comprehensive monitoring systems combining internal load (sRPE), external load metrics, and readiness indicators are essential for optimizing performance.